PENGARUH PENGGUNAAN MODEL PEMBELAJARAN CROSSWORD PUZZLE TERHADAP HASIL BELAJAR PPKn SISWA KELAS VII SMPN 6 MERANGIN DI DESA PINANG MERAH PROVINSI JAMBI - Putri Dwi Kumala; Sri Erlinda; Gimin Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the low student learning outcomes of PPKn at SMPN 6 Merangin. The formulation of the problem in this study is "is there any influence of the use of Crossword Puzzle learning models on learning outcomes whether students in class VII SMPN 6 Merangin?". This study aims to determine the effect of the use of Crossword Puzzle learning models in improving the learning outcomes of PPKn grade VII SMPN 6 Merangin. This research was conducted at SMPN 6 Merangin in July 2018.  This research is a quantitative descriptive research that was experimental. The population in this study were students of class VII SMPN 6 Merangin. The sample in this study was taken based on "Random Sampling" technique. where the classes taken into the sample were students of class VII C (experimental class) who were given a crossword puzzle learning model, and class VII A (control class) were students who were given conventional methods. Then the data were analyzed using homogeneity test and "t" test. The subject matter that is applied  is the "Norms and Justice". Based on the results of the study indicate that there is an influence of learning outcomes between students who use Crossoword Puzzle models and conventional methods in SMPN 6 Merangin  this can be seen from the results (>). Thus there is an effect of the use of Crossword Puzzle learning models on student learning outcomes VII. The magnitude of the effect after being calculated with a gain test shows the crossword puzzle leraning model gives an effect on learning outcomes of 0,5 in the medium category. Where there was an increase in the average learning outcomes of the experimental class to 84,56 and the average increase in the learning outcomes of the control class was 76,13. Key Words : Crossword Puzzle, Learning Outcomes